A self-standing nanoporous MoP2 nanosheet array: an advanced pH-universal catalytic electrode for the hydrogen evolution reaction. Issue 19 (22nd April 2016) - Zhu, Wenxin; Tang, Chun; Liu, Danni; Wang, Jianlong; Asiri, Abdullah M.; Sun, Xuping
Abstract : A self-standing MoP2 nanosheet array on carbon cloth acts as a robust pH-universal catalytic electrode for the hydrogen evolution reaction with high activity. Abstract : Electrochemical water splitting offers an environmentally friendly route for scalable production of hydrogen fuel but demands low-cost, efficient and robust electrocatalysts for the hydrogen evolution reaction (HER). In this communication, for the first time, we report on the development of a self-standing MoP2 nanosheet array on carbon cloth (MoP2 NS/CC) topotactically converted from its MoS2 NS/CC precursor through a phosphidation reaction. When used as a novel 3D HER cathode in acids, the resulting MoP2 NS/CC shows exceptionally high catalytic activity and strong durability, which only demands an overpotential of 58 mV to drive 10 mA cm −2 . Moreover, it also shows high activity and durability in basic and neutral media with the need for overpotentials of only 67 and 85 mV to achieve 10 mA cm −2, respectively. This MoP2 NS/CC catalytic electrode offers us an attractive catalyst material for water-splitting devices for large-scale hydrogen production.